GERAKAN LITERASI POLITIK PEREMPUAN NAHDLATUL ULAMA DALAM MENYAMBUT PEMILIHAN UMUM 2019-2020 - Syahputra, Muhammad Candra (JURNAL ISLAM NUSANTARA, 2020)
Pemilihan umum (Pemilu) is a five-year moment to elect the regional head, legislative, president and vice president as well as a democratic party in Indonesia. As a moment of political contestation in the Pemilu, in its implementasion is is often accompanied by violations committed by pairs of candidates who are contesting the election, such as money politics, politicization of SARA an so on. Nahdlatul Ulama as the largest community organization in Indonesia and even the world, plays an important role in carrying out political literacy in society, Nahdlatul Ulama women who are members of Pimpinan Wilayah Fatayat NU Lampung and Pengurus Koordinator Cabang Korps PMII Puteri Lampung Through political luteracy programs make a positive contribution in welcoming the Pemilu 2019-2020. This study uses qualitative approach, while the data sources were obtained through interviews, observations, documentation and literature related to the topic of discussion. The Nahdlatul Ulama Women’s Political Literacy Movement cooperates with the organizers of the Pemilu namely Komisi Pemilihan Umum (KPU) and Badan Pengawas Pemilu (Bawaslu) as a stakeholder. The Nahdlatul Ulama women through these programs aim to create a dignified democracy and be able to produce leaders who bring positive changes to the region and the country.